Antiangiogenic Effect of Salvia officinalis - Ahmed, Omar Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Angiogenesis plays a critical role in disease evolvement and exacerbations. This article has been prepared to evaluate the Antiangiogenic Effect of salvia officinalis that have been studied for their antiangiogenic activity. The plant sources of Iraq are likely to produce effective antiangiogenic substances. The phytochemical exploration of this plant has conferred to the discovery of new treatments for many disorders. Last year owing to the fear of adverse effects people favor the use of natural plant products for disease cure. This article also helps to summarize the different methodologies and various ways to evaluate the potential natural compounds having antiangiogenic action. The information collected here will take part in an essential role to develop new drug formulation for treatment angiogenesis-related diseases and further research should be done on the above mentioned plants.